T cells in the pathogenesis of ANCA-associated vasculitis: current knowledge - Hrusková, Z; Marecková, H; Ríhová, Z; Rysavá, R; Jancová, E; Merta, M; Tesar, V (Folia biologica, 2008)
AAV are a group of systemic immune-mediated diseases with a strong and highly specific association with ANCA. In recent years, there has been increasing evidence that ANCA might play a direct pathogenic role in triggering AAV. Nevertheless, effectors of cell-mediated immunity prevail in the inflammation sites in patients with AAV. Numerous studies found increased markers of T-cell activation in AAV. Moreover, this activation persisted even in remission and despite treatment. Finally, successful therapeutic attempts using T cell-directed treatment were also reported. There has therefore been substantial evidence that T cells are involved in the pathogenesis of AAV, even though the exact mechanisms are yet to be elucidated. In this review, recent findings on the contribution of T cells to the pathogenic processes in AAV will be briefly summarized. Special emphasis will be placed on the Th1/Th2 concept, the role of T-regulatory cells, and the role of effector memory T cells in the pathogenesis of AAV.
Keywords: Th2 buňky; Immunologic Memory; Antibodies, Antineutrophil Cytoplasmic; Peroxidase; cytokiny; Cytokines; Myeloblastin; Th1 Cells; Dendritic Cells; aktivace lymfocytů; dendritické buňky; vaskulitida; Humans; Lymphocyte Activation; peroxidasa; Th1 buňky; protilátky proti cytoplazmě neutrofilů; Th2 Cells; myeloblastin; imunologická paměť; T-Lymphocyte Subsets; T-lymfocyty - podskupiny; lidé; Vasculitis